Situation Report: Czechoslovakia, 16 March 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party Presidium Statement Further Dismissals: Kudrna, Bartuska Novotny's Fall Expected Shortly Demands for Postponement of Elections Censors Demand End of Censorship Barak to Report on Rehabilitations?